Glycometabolic Alterations in Secondary Adrenal Insufficiency: Does Replacement Therapy Play a Role? - Graziadio, Chiara; Hasenmajer, Valeria; Venneri, Mary A.; Gianfrilli, Daniele; Isidori, Andrea M.; Sbardella, Emilia (Frontiers in Endocrinology, 2018)
Secondary adrenal insufficiency (SAI) is a potentially life-threatening endocrine disorder due to an impairment of corticotropin (ACTH) secretion from any process affecting the hypothalamus or pituitary gland. ACTH deficit can be isolated or associated with other pituitary failures (hypopituitarism). An increased mortality due to cardiovascular, metabolic, and infectious diseases has been described in both primary and secondary adrenal insufficiency. However, few studies have provided compelling evidences on the underlying mechanism in SAI, because of the heterogeneity of the condition. Recently, some studies suggested that inappropriate glucocorticoid (GCs) replacement therapy, as for dose and/or timing of administration, may play a role. Hypertension, insulin resistance, weight gain, visceral obesity, increased body mass index, metabolic syndrome, impaired glucose tolerance, diabetes mellitus, dyslipidemia have all been associated with GC excess. These conditions are particularly significant when SAI coexists with other pituitary alterations, such as growth hormone deficiency, hypogonadism and residual tumor. Novel regimen schemes and GC preparations have been introduced to improve compliance and better mimic endogenous cortisol rhythm. The controlled trials on the improved replacement therapies, albeit in the short-term, show some beneficial effects on cardiovascular risk, glucose metabolism, and quality of life. This review examines the current evidence from the available clinical trials investigating the association between different glucocorticoid replacement therapies (type, dose, frequency and timing of treatment) and glycometabolic alterations in SAI.